The feasibility of simulation-based high-stakes assessment in emergency medicine settings: A scoping review - Loui K Alsulimani (Wolters Kluwer Medknow Publications, 2021)
Using simulation in high-stakes assessments has been evolving as a method to improve the assessment process. There is a concurrent need to address challenges and establish best practices to ensure the best quality when implementing high-stakes evaluations. The aim of this study is to provide an insight for stakeholders about using multiple modalities of simulation in high-stakes evaluations by presenting challenges, best practices, and future directions described in the relevant literature. A scoping review of original studies (from the year 1994-2021) including the use of common modalities (standardized patients, high-fidelity mannequins, part-task trainers, virtual simulation, and hybrid simulation) was conducted. The search covered the common databases: PubMed, Education Resource Information Center, Cumulative Index to Nursing and Allied Health Literature, and the Cochrane library. Initial screening in the databases resulted in 111,253 articles. After the application of a refining search strategy, 47 articles were included for comprehensive evaluation. Most articles were about credentialing/licensure purposes of assessment. Many articles were specialty-specific, especially focusing on anesthesia. Most challenges described were related to the validity of the assessment that should be considered in the planning phase. Best practices were mostly related to planning for measures to assure the validity of the assessment tools and process. The use of multimodality simulation for high-stakes assessment is growing despite challenges; this growth is associated with the accumulation of experience shared in literature. This growth will help to improve planning, practices, and goals achievement from such an application.